Assessment of Climate Change by Crop Yields - Burkhanov Bekhzod (Garuda Prestasi Nusantara Consulting, 2021)
With the United States producing 41% of the world's maize and 38% of the world's soybeans, the impact on US crop yields has implications for world food supply. We combine the US state results committee with a detailed climate information index that integrates the entire cycle between baseline and most extreme temperatures each day and throughout the day of the development season. The temperature rises to around 29 ° C for corn, 30 ° C for soybeans, and 32 ° C for cotton, but temperatures above this limit can be devastating. The slope of the attenuation towards the full ideal is more extreme than the slope below it. Similar non-linear and aberrant relationships can be seen taking into account the temporal arrangement of climate and yield or cross-sectional diversity. This suggests the possibility of limited variability in plant species given the fact that the last crop introduced the conversion of the farmer to a warmer environment, whereas the previous crop did not ... Considering current developing regions, normal yields by zone are expected to fall by 31-43% under slowing warming and 67-79% at the fastest-warming conditions before the end of this century.